2019
DOI: 10.1038/s41598-019-43890-4
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Heart Disease and ABO Blood Group in Diabetic Women: A Case-Control Study

Abstract: Numerous investigations conducted in general population have reported that certain ABO blood group may increase the risk of coronary heart disease (CHD). However, this association has not been yet well established and even is less clear in diabetic patients. Considering that women with type 2 diabetes mellitus (T2DM) are at greater risk to develop CHD and have higher cardiovascular mortality, this study aimed to evaluate the association between CHD and ABO blood group in women with T2DM. A case control study o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Besides, coronary heart disease was found to be less common among people with an O blood group (15). Compared to the O blood group, A, B, or AB blood groups have an increased risk of coronary heart disease by 5%, 11%, and 23%, respectively (18). The findings obtained in our study appear to be compatible with the literature.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Besides, coronary heart disease was found to be less common among people with an O blood group (15). Compared to the O blood group, A, B, or AB blood groups have an increased risk of coronary heart disease by 5%, 11%, and 23%, respectively (18). The findings obtained in our study appear to be compatible with the literature.…”
Section: Discussionsupporting
confidence: 90%
“…A, B, O blood group antigens as a potential independent risk factor for atherosclerotic plaque formation. At the same time thrombotic events, high systolic and diastolic blood pressure, and dyslipidemia could explain the relation between ABO blood groups and atherosclerosis (18).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a case-control study was introduced for the difference, and it has demonstrated that AB blood group has a higher odd ratio for the development of CAD and can be considered as a risk factor for the development of CAD in females with DM [21]. We believed that the association between ABO types and CAD risk might have sex-based difference in subjects.…”
Section: Discussionmentioning
confidence: 97%
“…Several pathways such as dyslipidemia, coagulopathy, inflammatory response (such as IL10, IL-6, and C-reactive protein), platelet aggregation and PCSK9 probably may contribute to the effect of ABO types on CAD [13,14,[21][22][23][24][25]. Mediation analysis indicates that around 10.5% of the effect of A blood group on CAD is mediated by TC levels [26].…”
Section: Discussionmentioning
confidence: 99%
“…32 ABO-Rh blood group system is linked to specific molecules in association with type 2 diabetes mellitus as the ABO blood group antigen especially A and B antigens enhances the general body inflammatory state as evidenced by many previous studies as they promote genetic mediation of single nucleotide polymorphisms at the ABO locus which are linked with soluble intercellular adhesion molecule 1, Eselectin, P-selectin, tumor necrosis factor 2 along with other inflammatory markers which set up an acute phase response with increased hepatic production of C-reactive protein leading to insulin resistance in the liver, skeletal muscle, vascular endothelial tissue along with other sites of a human body and ultimately leading to the development and progression of type 2 diabetes mellitus. 33,34 It is worth noting that the search for disease-blood group association has often been criticized as studies on different populations have often failed to confirm initial reports. It is note-worthy yet there lies a large possibility that such inconsistencies are due to vastly different environments in study populations.…”
Section: Discussionmentioning
confidence: 99%